Drivers of Organizational Performance in Accounting Firms: Price Competition, Professional Standards (SPJA) Effectiveness, and Firm Reputation under the Moderating Role of Professional Regulation - Wijono, Monica Widyati; Harianto, Eric; Tambunan, Damelina Basauli (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Accounting Service Firms (KJA) play a vital role in supporting SMEs in Indonesia, yet they face challenges from price competition and dynamic of accountant professional regulations. This study aims to analyze the effects of price competition, the effectiveness of implementing the Standards of Accountants Services (SPJA), and reputation on organizational performance, with the regulation of the accounting profession as a moderating variable. A quantitative approach with an explanatory survey was employed, targeting 500 KJA registered on the Find KJA IAI Global platform as of May 5, 2025, with 144 firms participating. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that price competition and effective SPJA implementation have positive and significant effects on organizational performance, whereas firm reputation does not show a significant effect. Moreover, accountant professional regulation does not strengthen these relationships; instead, it tends to weaken the effect of SPJA effectiveness on performance. These results suggest that for small-medium scale KJA, accountant professional regulations are perceived more as an administrative burden than as strategic support. This study underscores competitive pricing and effective SPJA implementation as the main drivers of KJA performance, while reputation has yet to emerge as a determining factor. Theoretically, the findings challenge the relevance of Public Interest Theory and Interest Group Theory in the context of smaller KJA, while practically highlighting the need for proportional regulations that focus on strengthening internal capabilities.